Pengaruh Pemberian Kredit Usaha Rakyat Terhadap Pendapatan Usaha Mikro Kecil Dan Menengah - Nita Y Adju; Harun Blongkod; Nurharyati Panigoro (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2023)
This study aims to determine how much influence the provision of people's business credit (KUR) has on the income of micro, small and medium enterprises (UMKM). This research uses quantitative methods. The data used is primary data obtained from distributing questionnaires. The population of this research is UMKM BRI Unit Aloei Saboe customers, Gorontalo City. The sampling technique used purposive sampling. The data analysis method used is Structural Equation Modeling (SEM). The results of this study indicate that the provision of people's business credit (KUR) has a significant effect on the income of micro, small and medium enterprises (UMKM) on BRI Unit Aloei Saboe UMKM customers, Gorontalo City.